A 25 mg rectal dose of diclofenac for prevention of post-ERCP pancreatitis in elderly patients. (2nd September 2021) - Maeda, Natsumi; Higashimori, Akira; Nakatani, Masami; Mizuno, Yuki; Nakamura, Yoshihiro; Ikeda, Daisuke; Maruyama, Hirotsugu; Morimoto, Kenichi; Fukuda, Takashi; Watanabe, Toshio; Fujiwara, Yasuhiro
Abstract: Objectives: A 50–100 mg rectal dose of diclofenac or indomethacin is recommended for prophylaxis of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP); however, limited data are available regarding the appropriate dose to prevent PEP in elderly patients. We aimed to evaluate the efficacy and safety of 25 mg diclofenac in preventing PEP in elderly patients. Material and methods: Overall, 276 patients with naive papilla, aged over 75 years, were included in the present study between April 2013 and March 2020. We retrospectively evaluated the risk of PEP in patients over 75 years, administered with or without 25 mg diclofenac 30 min before ERCP using inverse probability of treatment weighting (IPTW) analysis. Results: Patients were categorized into the diclofenac group (83 patients) or non-diclofenac group (193 patients). The incidence rate of PEP in the diclofenac group was significantly lower than that in the non-diclofenac group (4% vs . 14%, p = .01). Multivariate analysis revealed that 25 mg diclofenac was an independent protective factor against PEP in elderly patients aged over 75 years (odds ratio [OR] = 0.17; 95% confidence interval [CI] = 0.04–0.67; p = 0.01). This protective effect of diclofenac against PEP remained robust after IPTW analysis (OR = 0.11; 95% CI = 0.03–0.40; p = .001). No adverse events related to diclofenac were observed. Conclusion: Diclofenac (25 mg) was considered effective and safe for preventing PEP in elderly patients. Our results may provide a new strategy for preventing PEP in elderly patients.